PERAWATAN WARISAN BUDAYA: MEMBANGUN MASA DEPAN BANGSA SEBUAH PENELITIAN PENDAHULUAN (Preservation of Cultural Heritage: Building The Future of The Nation a Preliminary Study) - I Made Sutaba (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2019)
Indonesia is well known to all over the word as a very rich country of cultural heritage that spread all over the island. Among them, there are an important tangible and intangible archaeological heritage. As historical heritage, this cultural is a valuable source of pluralistic information of the past life of our ancestor. Learning his historical evident, there are remarkable problems that is impossible for me to study it now, for example problem of typology, function and so on. In this study we decided to learn only the preservation and protection of cultural heritage and its relevant relationship for building he future of the nation, which has not investigate yet until now. Facing the future, cultural heritage that bear a significant socio-cultural values are increasingly important for buiding the future of our nation. By studying the problems, this study aims is to predict the problems. To achieve this goals, the study through library research along with archaeological and SWOTS approach. The result show that preservation and protection of cultural heritage has an important relationshil for building the future of the nation.ABSTRAKIndonesia terkenal di seluruh dunia, adalah negeri yang kaya raya akan warisan budaya yang tersebar hampir di seluruh kepulauan. Di antara warisan budaya ini, terdapat cabar budaya yang tergolong tangible dan intangible. Sebagai bukti sejarah, warisan budaya ini adalah sumber informasi yang sangat berharga bersifat pluralistik mengenai kehidupan masa lalu nenek moyang kita. Mencermati bukti-bukti sejarah ini mengandung permasalahan yang tidak mungkin kami teliti dewasa ini, seperti masalah tipologi, fungsi dan lain-lainnya. Dalam penelitian ini, kami memutuskan hanya meneliti mengenai perawatan dan perlindungan warisan budaya dan relevansinya bagi pembangunan masa depan bangsa. Menghadapi masa depan, warisan budaya ini mengandung nilai-nilai sosial-budaya yang signifikan, menjadi semakin penting untuk pembangunan masa depan bangsa kita. Mempelajari permsalahan in, penelitian ini bertujuan untuk meneliti permasalahan ini. Untuk mencapai tujuan ini, penelitian dilakukan melalui kajian pustaka yang disertai dengan pendekatan arkeologi dan SWOTS. Hasil penelitian ini menujukkan, bahwa perawatan dan perlindungan warisan budaya mempunyai hubungan relevansi yang angat penting bagi pembangunan masa depan bangsa kita.